Performance of a novel football helmet technology on head impact kinematics - Yount, D. L.; Jesunathadas, M.; Plaisted, T. E.; York, S.; Edwards, E. D.; Gould, T. E.; Chatham, L. S.; Piland, S. G. (Sports Engineering, 2021)
In the effort to reduce concussions in American football, helmet manufacturers are seeking new technologies to reduce peak head impact kinematics. However, the efficacy of these new helmet technologies is unknown. Therefore, the purpose of this study was to evaluate the influence of an intermediary liner on the blunt impact kinematic performance of an American football helmet using a custom test similar to the NOCSAE (ND-081) and NFL linear impactor test methods. Twelve Schutt F7 football helmets with the Radian Diffusion System technology were evaluated under three conditions: with the system (hypothesized to function as a slip plane), without the system, and with a modified system using cloth to cover the hook and loop attachment that, by design, mechanically adheres the system to the comfort liner of the helmet. Helmets were impacted three times at 6 m/s (281 J) at six locations [side, rear boss non-centroidal, rear boss centroidal, rear, front boss, and a random location used for all helmets] using a pneumatic ram. While an effect was found for linear accelerations at the Rear, Rear Boss Center of Gravity, Rear Boss Non-Centroidal, and Random locations, no overall differences between liner conditions were observed for peak resultant linear (p = 0.310) and angular accelerations (p = 0.231), or peak resultant angular velocity (p = 0.127).